ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen Chicken Nugget Fiesta di Kota Semarang) - Wirawan, Edwin Muhammad; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2016)
Community life in the urban dynamic makes people choose foods that are practical. Manufacturers chicken nuggets Fiesta is one of the manufacturers of ready cooked meals of chicken nuggets. In a period of three years back chicken nuggets Fiesta compete with other similar products and led to a decline in sales. This study aimed to analyze the effect of product quality, perceived price, promotion and brand image on purchasing decisions chicken nuggets Fiesta in Semarang.The samples used in this study of 100 people who have ever made a purchase products Fiesta chicken nuggets in Semarang. Questionnaire distributed in April 2016 to May 2016. The data were then processed using multiple regression analysis.The results showed that the product quality, perceived price, promotion and brand image has a positive influence on purchase decisions. Variable most influential product quality and perception variables affect the price of the smallest. T test results showed that each of the independent variables have a significant influence on purchasing decisions. This equation model has a F value of 24.726 with a significance level of 0.000. The results of the analysis of determination coefficient of 48.9%, indicating that the variable quality of the product, the perception of price, promotion and brand image just explain the influence on purchasing decisions by 48.9%. While the remaining 51.1% is explained by other variables that are not described in this study.